Lū se lū phracʻ vādānuvāda vinicchaya : Theravāda cvayʻ cuṃ kyamʻʺ (Sāsanā reʺ Ūʺ cīʺ Ṭhāna, 1981)
Proceedings of a debate in the presence of a state appointed commission of monastics to investigate and decide the misbeliefs and misinterpretations of the Buddhist doctrines propagandized by a research institute Sammadiṭṭhi Sutesana ʼA phvaiʹ khyupʻ, headed and motivated by Lū se lū phracʻ Cha rā Ūʺ Ukkaṭṭha.